Korelasi Sikap Belajar Dengan Hasil Belajar Siswa: Studi pada Sekolah Menengah Pertama Negeri 10 Kotabumi - Darwanto D; Kiki Herdiansyah (Universitas Muhammadiyah Kotabumi, 2022)
The mindset of learning outcomes that most ordinary people know is only limited to the values ​​of the tests that have been carried out. So it still happens that teachers only focus on learning outcomes in the cognitive domain. Whereas the distribution of learning outcomes has 3 domains, namely cognitive, affective, and psychomotor. This research is a quantitative research with correlation technique. The population in this study were all grade VIII students of SMP Negeri 01 Kotabumi for the academic year 2020/2021, totaling 317 students. The sample of this study amounted to 79 students. The sampling technique used a proportionate stratified random sampling technique. The learning attitude instrument uses a questionnaire/questionnaire. Meanwhile, the learning outcomes instrument used a multiple choice test. Hypothesis test using Product Moment Correlation. For the correlation analysis of learning attitudes and learning outcomes, it produces a correlation coefficient (r_xy) of 0.2341 and r_(table(79)(0.05)) of 0.2210. This shows that there is a correlation (relationship) of learning attitudes (affective learning outcomes) and mathematics learning outcomes (cognitive domains).